2016
DOI: 10.1016/j.jmii.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction-restriction fragment length polymorphism method for differentiation of uropathogenic specific protein gene types

Abstract: The putative pathogenicity island (PAI) containing the uropathogenic specific protein (usp) gene and three small open reading frames (orfU1, orfU2, and orfU3) encoding 98, 97, and 96 amino acid proteins is widely distributed among uropathogenic Escherichia coli (UPEC) strains. This PAI was designated as PAIusp. Sequencing analysis of PAIusp has revealed that the usp gene can be divided into two types - uspI and uspII - based on sequence variation at the 3' terminal region and the number and position of orfUs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In this study, we found that the positive rate of double J tube bacterial culture of patients in both groups was higher than that of bladder and urine bacterial culture. Furthermore, the bacteria cultured in double J tubes were mainly GNB, Escherichia coli , followed by GPC, which was consistent with previous research results [ 52 , 54 , 55 ]. Combined with above data, it can be considered that continuous indwelling catheterization can reduce the number of bacteria colonized in the double J tube, thus reducing the incidence of urinary tract infection.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the positive rate of double J tube bacterial culture of patients in both groups was higher than that of bladder and urine bacterial culture. Furthermore, the bacteria cultured in double J tubes were mainly GNB, Escherichia coli , followed by GPC, which was consistent with previous research results [ 52 , 54 , 55 ]. Combined with above data, it can be considered that continuous indwelling catheterization can reduce the number of bacteria colonized in the double J tube, thus reducing the incidence of urinary tract infection.…”
Section: Discussionsupporting
confidence: 92%
“…PAIs consist typically of VAGs encoded within chromosomal regions and are capable of being exchanged via horizontal gene transfer [52]. Among our isolates, we detected malX and usp, located on PAI I CFT073 and PAI usp , in 100% and 75.9% of the isolates, respectively [53,54]. Usp has been associated with UTI isolates and is suggested as a potential VAG for use as a molecular epidemiological marker specific for UPEC.…”
Section: Discussionmentioning
confidence: 77%
“…They encode virulence proteins such as toxins, adhesins, and invasins, which allow bacteria to colonize and damage host tissues. The presence of the USP virulence gene in such a high proportion of E. coli isolates suggests an elevated potential for pathogenicity and the ability to cause disease in the context of wound and burn infections [3]. Because females spend the majority of their time in the kitchen, where accidents are common, the incidence of burns was higher in females.…”
Section: Discussionmentioning
confidence: 99%
“…Journal for Research in Applied Sciences and Biotechnology www.jrasb.com stay than surgical wounds [3]. Infection is a major cause of morbidity and mortality in hospitalized burn patients [4,5].…”
Section: Issn: 2583-4053mentioning
confidence: 99%